A Retrospective Analysis of Risk Factors Associated with Road Traffic Accident Fatalities - MUHAMMAD SAFDAR LUQMAN,; UMAR TANVEER,; BILAL AHMAD QURESHI,; ASIFA ZEBA,; NAYAB TANVEER,; SAMEER BADRI AL-MHANNA, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Road traffic accidents (RTAs) are a leading cause of death globally, with millions of people affected each year. Understanding the factors contributing to fatalities in RTAs is essential for designing preventive strategies. While several factors such as speeding, alcohol consumption, and road conditions have been implicated, their relative contribution to fatal outcomes remains underexplored. Objective: The objective of this study was to identify and evaluate the risk factors associated with fatal outcomes in RTAs by analyzing data from 250 patients involved in severe accidents. Methodology: A retrospective observational study was conducted in Gujranwala from 15 January to 15 March, focusing on 250 patients who suffered severe injuries or fatalities due to road traffic accidents (RTAs). Data were extracted from hospital medical records and included patient demographics, accident circumstances, alcohol use, speeding, seatbelt utilization, as well as weather and road conditions. Injury severity was also recorded. Statistical analysis was performed using SPSS version 25.0, employing descriptive statistics and logistic regression to identify significant associations. Results: The study found that 137 of the 250 patients died from their injuries, representing a 55% fatality rate. Significant risk factors identified included alcohol consumption (72% fatality rate), speeding (65% fatality rate), and seatbelt non-use (78% fatality rate). Logistic regression analysis revealed that alcohol consumption, speeding, and seatbelt non-use were the most significant predictors of fatality. Conclusion: Alcohol consumption, speeding, and the non-use of seatbelts were the primary risk factors associated with fatality in RTAs. Public health interventions and law enforcement measures targeting these behaviors could significantly reduce road traffic fatalities.